Spatiotemporal heterogeneity of soil fertility in the Central Monte desert (Argentina) - Abril, Adriana (2009)
In arid environments, soil fertility exhibits a high degree of spatial and temporal heterogeneity, which results from high climatic variability seasonally and heterogeneous plant distribution. However, because most desert areas have been altered by human activities, heterogeneous fertility would originate from grazing or logging activities. We evaluated spatial and temporal heterogeneity of soil fertility in cattle-excluded sites under and outside woody plant cover (Prosopis flexuosa and Larrea divaricata), and in sites disturbed by tree removal during wet and dry season in Ñacuñán Biosphere Reserve (Central Monte desert of Argentina). Soil organic matter, fulvic acids, bioavailable organic matter, and nitrate were lower outside plant canopy (8.9 mg g-1, 0.03 mg g-1, 8.2 mg g-1, and 4.17 mg kg-1, respectively). Total N, humic acids, and abundance of microbial functional groups did not show differences among sites. Most parameters differed between seasons, tending to be higher in the wet season. Overall soils of Ñacuñán Reserve are characterized by: a) more homogenous spatial pattern than expected from woody plant presence; b) very heterogeneous temporal pattern; and c) after two years, tree removal does not seem to induce infertile soil formation.